A triplication of the Williams–Beuren syndrome region in a patient with mental retardation, a severe expressive language delay, behavioural problems and dysmorphisms. Issue 4 (14th September 2009) - Beunders, Gea; van de Kamp, Jiddeke M; Veenhoven, Reinier H; van Hagen, Johanna M; Nieuwint, Aggie W M; Sistermans, Erik A
Abstract : Background: Intrachromosomal triplications are rare chromosomal rearrangements. In most triplication cases the phenotype is similar to, but more severe than observed in patients with a duplication of the same region. The Williams-Beuren syndrome (WBS) region on 7q11.23, is prone to chromosomal rearrangements. A common deletion causes the well-characterised Williams-Beuren syndrome. The reciprocal duplication has been described in 27 families only, and is associated with a variable phenotype, including speech delay with (mild) mental retardation, autism and mild dysmorphic features. As the duplication of the WBS region is sometimes found inunaffected parents, initially some doubts have been raised about the pathogenicity of the duplication. Results and methods: We here describe the first triplication of a large part of the WBS region, detected with array CGH and confirmed by MLPA and FISH. The phenotypic features include mental retardation, a severe expressive language delay, behavioural problems and dysmorphisms. Conclusion: These features are remarkably similar, but seem more severe, compared to features seen in duplication patients. Therefore, our findings support the idea that an amplification of the WBS region is a disease-causing event, although the penetrance might be incomplete.